Parenting Patterns Have a Relationship with the Risk of Language Development Delays in Preschool Children at Permata Ilham Kindergarten - Nuhan, Helena Golang; Hardianti, Wini Fuji (LPPM Universitas Mohammad Husni Thamrin, 2025)
Background: Language development in children aged 4-5 years is often found to experience obstacles, in the form of articulation disorders, words or vocabulary, sound production. One of the reasons why children are late to speak is minimal interaction with parents. Lack of parental stimulation of children can also inhibit speech development in children, meaning here that parents are too busy working and do not have time to communicate with their children. Objective : of this study was to determine the relationship between parenting patterns and the risk of delayed language development in preschool children. Method: This study used a quantitative method with a cross-sectional design. The research sample consisted of 101 preschool children. Data were collected using a questionnaire that included parenting patterns and the risk of delayed language development. Data analysis was carried out using the chi-square test. Results: age of children 5 years (59.4%), gender of male child (53.5%), age of parents middle adulthood (50.5%), gender of parents female (81.2%), education (89.1%), work (51.5%), >UMP (57.4%), democratic parenting (52.5) no risk of delay (73.3%) The results of the analysis showed a significant level of 0.000, stating that there is a relationship between parenting patterns and the risk of delayed language development in preschool children at TKIT Permata Ilham Bekasi in 2025. Conclusion: Nurses and health workers can play a role in providing education to parents on how to stimulate children's language from an early age, including through reading books together, talking to children actively, and avoiding excessive use of gadgets.